Філософські підходи до поняття динаміки культури - Овчиннікова, Альбіна Петровна; Овчинникова, Альбина Петровна; Ovchinnikova, Al'bina (My University, 2013)
The article characterizes the dynamics of culture in the modern sense; fundamental phenomena that permeate all elements of culture and organize them into a coherent system may be revealed within complex system of cultural events of every historical epoch.
Овчиннікова А. П. Філософські підходи до поняття динаміки культури / А. П. Овчиннікова // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2013. – Т. 13. – С. 132-141.
Keywords: динаміка культури; синергетика; артефакт; "тип культури"; "виклик"; "відповідь"; цивілізація; еволюція; динамика культуры; "тип культуры"; "вызов"; "ответ"; цивилизация; эволюция; dynamics of culture; synergy; artifact; «type of culture»; «challenge»; «answer»; civilization; evolution